2018
DOI: 10.1002/qua.25710
|View full text |Cite
|
Sign up to set email alerts
|

Coupled cluster theory with the polarizable continuum model of solvation

Abstract: The environment may significantly affect molecular properties. Thus, it is desirable to account explicitly for these effects on the wave function and its derivatives, especially when the latter are evaluated with accurate methods, such as those belonging to coupled cluster (CC) theory. In this tutorial review, we discuss how to combine CC methods with the polarizable continuum model of solvation (PCM). We describe useful approximations that include the solvent response to the correlation and excited state equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 95 publications
(254 reference statements)
0
24
0
Order By: Relevance
“…This review is focused on the theoretical framework and computational mechanics of continuum solvation models, not on applications. Some limited data are provided in order to describe the performance of the models, but the reader is directed to several general reviews for a more complete overview of continuum solvation methods in action 8,13–15,26–28 . Other, more specialized reviews describe the application of PCMs to specific types of spectroscopy 29–35 .…”
Section: Overviewmentioning
confidence: 99%
“…This review is focused on the theoretical framework and computational mechanics of continuum solvation models, not on applications. Some limited data are provided in order to describe the performance of the models, but the reader is directed to several general reviews for a more complete overview of continuum solvation methods in action 8,13–15,26–28 . Other, more specialized reviews describe the application of PCMs to specific types of spectroscopy 29–35 .…”
Section: Overviewmentioning
confidence: 99%
“…The latter also reported a mixed implicit/explicit EOM solvent model as well as benchmark results on PCM–EOM . Caricato's recent review is also a useful guide to the field . It should be noted that when PCM is added, the EOM and linear response treatments yield different results .…”
Section: Algorithmic Approximationsmentioning
confidence: 99%
“…It should be noted that when PCM is added, the EOM and linear response treatments yield different results . In particular, the latter depends on the transition density of the solute and can be recommended for the description of transition properties, while in the former approach the solvent responds to the excited state density of the solute and thus it is also called state specific since for each state it provides a better description of the mutual polarization between solute and solvent . A different implicit solvent model, the conductor‐like screening model (COSMO) was also implemented for the ADC(2) method recently .…”
Section: Algorithmic Approximationsmentioning
confidence: 99%
“…All calculations reported in the main text are performed in the gas phase. Treatments of solvent through implicit and/or explicit methods can be very successful (Hush and Reimers, 2000 ; Tomasi, 2011 ; Mennucci, 2012 ; Skyner et al, 2015 ; Zuehlsdorff and Isborn, 2018 ; Caricato, 2019 ; Cerezo et al, 2020 ), but no such approach has been demonstrated as yet to be successful for understanding chlorophyll bandshapes. Indeed, results presented in Supplementary Table 1 using commonly applied solvation treatments fail to provide qualitatively useful information, as has been previously noted for bacteriochlorophyll-a (Higashi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%